Analisis Faktor–Faktor yang Mempengaruhi Kekalahan Calon Legislatif dalam Pemilu 2024 - Rizka Sahbania; Ita Rosita Wahyiah; Mohamad Ikrom Arasid; Ayu Fadilah; Hani Apriliyani; R. Syehan Ali Al Farez; Shelina Mahwi (UNIVERSITAS SERAMBI MEKKAH, 2024)
In the context of Indonesian politics, the 2024 General Election marks an important event that presents intense competition between legislative candidates from various political parties. Failure in the election is not only inevitable but also brings significant impacts. Through a qualitative approach, this study aims to explore and analyze the impact of losing candidates in the 2024 elections, especially in the psychological, social, and political aspects. The findings of this study show that losing a candidate can result in feelings of disappointment, frustration and even depression on a psychological level. On the social side, the defeat can disrupt relationships with supporters and campaign volunteers and cause stigmatization in the candidate's social environment. Politically, losing a candidate can affect the dynamics of political parties and political competition as a whole.